Distribution of soil moisture on slopes of an agroforestry landscape complex - Tarasov Anatoly; Podlesnykh Igor; Tarasov Sergey; Kaluzhskih Alexander (E3S Web of Conferences, 2025)
This study investigates the impact of a soil-protective agroforestry landscape complex on soil moisture distribution across different topographical positions. Experimental data collected from 2020 to 2024 were analyzed to compare moisture reserves in the top meter of soil on a watershed plateau and along the middle and lower sections of a west-facing slope. Two watersheds were examined: a control site without erosion control measures and an experimental site featuring runoff-regulating forest belts. The research was conducted on typical heavy loamy chernozem soil. Results revealed that in the control watershed, lacking forest belts, maximum moisture reserves consistently accumulated at the slope’s base due to subsurface lateral flow. In contrast, the watershed with the agroforestry complex exhibited a more uniform moisture distribution across topographical elements, with significantly reduced downslope water movement. This enhanced moisture retention is attributed to the forest belts’ ability to mitigate subsurface lateral flow towards the slope’s foot. These findings underscore the effectiveness of agroforestry systems in regulating soil moisture distribution, potentially improving water resource management and erosion control in agricultural landscapes.